Growth performance and flesh quality of tilapia (Oreochromis niloticus) fed low concentrations of Rubrivivax gelatinosus, Saccharomyces cerevisiae and Spirulina platensis - Grassi, Thiago Luís Magnani [UNESP]; Paiva, Natália Mingues [UNESP]; Oliveira, Dayse Lícia [UNESP]; Taniwaki, Fábio [UNESP]; Cavazzana, Jefferson Felipe [UNESP]; da Costa Camargo, Gisele Cristina Rocha [UNESP]; Diniz, Juliana Campos Pereira [UNESP]; Bermejo-Poza, Rubén; Borghesi, Ricardo; Villarroel, Morris; Ponsano, Elisa Helena Giglio [UNESP] (Springer Nature, 2020)
Saccharomyces cerevisiae biomass generated as a by-product in industrial processes and other biomasses grown in industry waste waters like Spirulina platensis and Rubrivivax gelatinous can be used in aquafeed, thus reducing the costs of discard and minimizing environmental damage. In this study, 840 male Nile tilapias (Oreochromis niloticus; 26.8 ± 1.03 g average weight) were distributed among 21 tanks (40 fish/tank, 1.07 kg/m3). Fish were fed to satiation three times a day throughout the trial (72 days). A completely randomized design experiment with 7 treatments (control group and 6 different diets, 3 replicates per treatment) was conducted to investigate the effects of these three microbial biomasses (added at 0.25 and 0.5% into an isoproteic/isoenergetic tilapia diet) on the growth and visceral indexes of the fish and on the composition and texture of the fillets. Feed conversion ratio was significantly lower in fish fed 0.5% R. gelatinosus than that in the control group, but no difference was detected among the treatments either for the other growth indicators or for the organs’ indexes. Including microbial biomass in the diet did not significantly affect either fillet pH or texture parameters. However, the use of microbial biomass increased the protein content and decreased the n-6/n-3 ratio of the fillets compared with that of the control group. So, it was concluded that the dietary intake of low concentrations of S. cerevisiae, S. platensis and R. gelatinosus biomasses did not affect the growth performance of tilapias, increased the nutritional quality and preserved the texture features of the fillets.
Keywords: Feed formulation; Growth metrics; Microbial biomass; Proximate chemical composition